Economic Linkages and Supply Chain Analysis of Date Palm in Baluchistan (Journal of Asian Development Studies, 2024)
The date palm is an essential fruit in Pakistan, economically and religiously valued. Thriving in hot climates, it grows well in southern Punjab and Baluchistan, serving as a crucial food source. This study evaluates the Economic Linkages and Supply Chain Analysis of Date palms in Baluchistan. The respondents included stakeholders, such as growers, wholesalers, and retailers, with a sample size of 102 individuals. Data were collected through well-structured interview schedules tailored for each stakeholder group and analyzed using the Statistical Package for the Social Sciences (SPSS). The findings reveal that Panjgur growers produced more than Kech. Regarding experience, 66.7% of Kech wholesalers had 6 to 15 years of experience, compared to 53% in Panjgur. Additionally, 33.4% of Kech wholesalers had over 15 years of experience, whereas this was true for 26.7% in Panjgur. Panjgur wholesalers spent more on purchasing date palms than those in Kech. Income-wise, about 13% of Kech wholesalers earned up to ten lakhs, with one-third of Panjgur wholesalers in this category. Meanwhile, 47% of Kech wholesalers earned between ten and thirty lakhs, compared to 40% in Panjgur. Retailers in Kech reported higher profits, with 84% earning more than 250,000 rupees, while 66.7% of Panjgur retailers earned over 250,000 rupees. There is a need to enhance stakeholders' production and marketing strategies. Specifically, growers should be equipped with modern technology to increase their profit margins and reduce fruit wastage.